Fume Formation Rate Analysis of Shipbuilding Steel with SMAW Using Taguchi Design and ANOVA - Mert, T.; Ekinci, S. (POLISH ACAD SCIENCES INST PHYSICS, 2017)
Shipbuilding industry grows rapidly due to the increasing growth of economies and thus, the need for new and bigger ships emerge. Manufacturing of ships in shipyards includes harmful processes, such as welding, which impact the workers and the environment. As a consequence of increase in demand for new ships, deleterious welding fume and emissions all over the world increase year by year. Welding fume includes hazardous micro and sub-micro sized metal particulates and in addition to welding fume, welding emissions consist of detrimental gaseous wastes as well. In this study, a set of experiments was designed by Taguchi method. These experiments were realized by two welders using two different types of covered electrodes (rutile and cellulosic), welding speeds and currents on Grade A shipbuilding steel, which is one of the most common steels in shipbuilding. After the experiments, fume formation rate was measured and it was observed that the contributions of the factors are 9 2.4 7%, 5.42% and 1.66% for electrode type, current and welder, respectively. The results were assessed using Taguchi and ANOVA and evaluated in terms of environment and occupational health and safety.
Keywords: WELDING FUME; EMISSION ESTIMATION; NEUROLOGICAL RISK; EXPOSURE; SIZE; Physics